Evaluating the quality of culinary tourism: Challenges and consumer perceptions - Putri Indah Husnul Khotimah; Marcella Claresta Wahjudi; Nanda Syhalom Ramli (Journal of Rural Tourism, 2025)
Purpose - The purpose of this research is to understand consumer perceptions and identify challenges in maintaining service quality in culinary tourism. It focuses on the challenges faced at Kopi Klotok, a culinary tourism destination.Methodology/Design/Approach - The study uses a qualitative approach, employing a literature study method to review academic journals and previous research on culinary tourism and quality management. Additionally, secondary data is analyzed from online review platforms such as social media and Google Reviews. The research also includes direct observation of the existing service process at Kopi Klotok. Finding - The study identifies several challenges that affect service quality, such as inconsistent service during peak hours, limited seating capacity, and long waiting times. These issues negatively impact the customer experience. The secondary data analysis also reveals that while consumers perceive traditional environments as offering authentic experiences, overcrowding and inadequate service management can disrupt this perception.Originality/Value - This research highlights the importance of operational efficiency and service consistency in maintaining customer satisfaction in culinary tourism. It emphasizes the need for effective service management to address the challenges faced during peak times and ensure a positive customer experience.